Selectivity of the herbicide flazasulfuron applied after postemergence in sugarcane (Saccharum spp. L.) crop - Durigan-Marcel, E. B.; Durigan, Julio Cezar [UNESP]; Gustavo, M. (Marcel Dekker Inc, 2005)
The selectivity of the herbicide flazasulfaron was evaluated when applied at two rates (50 and 100 g/ha) with and without surfactants (Aterbane or Agral at 0.2% v/v). The treatment was applied at early (three leaves) and late (five to six leaves) stages of the postemergence of sugarcane plants (var. RB845257) grown in two soils (sandy and clay) with good moisture status before and after application. Despite the toxicity symptoms, especially at the late stage with the higher rate of application in the sandy soil, the herbicide did not affect the growth nor the stalk yield. The presence of the surfactants had no effect on the toxicity symptoms.
Keywords: chemical control; application stages; surfactants; soil texture